Slope monitoring of large scale experiment of undercut slope at Mae Moh Mine, Thailand - N. Mavong (2018)
Electricity Generation Authority of Thailand (EGAT)'s Mae Moh mine is one of the largest surface mines in Southeast Asia. Its annual production is approximately 15 million tons of lignite and 90 million m 3 of waste. The complexity of geological structures causes a number of geotechnical difficulties. Typically, lignite exploitation makes the weak green clay seam Gl seam, daylighted along the footwall, and possibly causes a massive failure of underburden claystone. The Cut and Fill mining technique has been initiated as a large scale field experiment at the Mae Moh mine's northeast footwall slope, which is estimated to be a 3 million m 3 of potential sliding block. With this technique, the Gl interface will be partially daylighted. Therefore, arch formation is formed in the sliding block and could perform as a temporary support at a certain undercut span width. This was studied using 3DEC, a 3D numerical analysis code. To date, this mining area is under construction and a monitoring program has been installed with an automatic deformation monitoring system, inclinometers, and piezometers. The purposes of the monitoring program were not only for collecting the behavior of displacement and water pressure in the partially undercut slope, but also to perform as a criterion for failure warning system during mining operation. The monitoring data obviously shows that the displacement of the undercut slope related to the undercut operation and the precipitation amount. This field monitoring data is useful to make a better understanding of the undercut slope behavior at Mae Moh mine. Moreover, it can be used for improving the 3D numerical analyses more accurately by calibrating the key mechanical properties of the rockmass at Mae Moh mine. Copyright 2013 ARMA, American Rock Mechanics Association.